2021
DOI: 10.1093/socpro/spab027
|View full text |Cite
|
Sign up to set email alerts
|

Criminalized or Medicalized? Examining the Role of Race in Responses to Drug Use

Abstract: Drug policy has shifted from intense criminalization toward reforms that prioritize decarceration and treatment. Despite this shift, little is known about whether support for recent treatment-oriented drug policy is equitable by users’ race and the drug type. Using the opiate and crack cocaine crises as cases, we analyze 400 articles from the New York Times and Washington Post to assess the degree to which the two crises were racialized, criminalized, and medicalized. We find that media coverage medicalized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…52,53 Racialized framing may have ultimately contributed to public support for criminalization during the crack cocaine crisis but medicalized approaches to drug use during the opioid crisis. 54 In this study, low numbers of minority OUD patients precluded formal analysis of differences in coverage by race, but, anecdotally, the coverage appeared to be consistently sympathetic to patients across races. In this way, the lack of adequate racial representation of minority OUD patientsgenerally presented as victims to powerful opioidsis consistent with reduced media attention to minority victims of crimes.…”
Section: Agenda Setting In Opioid-related News Coveragementioning
confidence: 74%
See 1 more Smart Citation
“…52,53 Racialized framing may have ultimately contributed to public support for criminalization during the crack cocaine crisis but medicalized approaches to drug use during the opioid crisis. 54 In this study, low numbers of minority OUD patients precluded formal analysis of differences in coverage by race, but, anecdotally, the coverage appeared to be consistently sympathetic to patients across races. In this way, the lack of adequate racial representation of minority OUD patientsgenerally presented as victims to powerful opioidsis consistent with reduced media attention to minority victims of crimes.…”
Section: Agenda Setting In Opioid-related News Coveragementioning
confidence: 74%
“…White pregnant drug users were more likely to be presented as guilt-ridden and committed to successful treatment, while Black women were often characterized as depleted and/or bad mothers 52 , 53 . Racialized framing may have ultimately contributed to public support for criminalization during the crack cocaine crisis but medicalized approaches to drug use during the opioid crisis 54 . In this study, low numbers of minority OUD patients precluded formal analysis of differences in coverage by race, but, anecdotally, the coverage appeared to be consistently sympathetic to patients across races.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were then asked whether the person in the vignette should be charged with a crime or assigned to drug treatment. The authors found that people were more likely to support criminalization for Black persons regardless of the type of drug used and drug treatment for white persons [74]. Furthermore, policy research finds that people who hold more negative attitudes toward Black people (i.e., racial stigma) have decreased odds of supporting public health policies addressing opioid use [75].…”
Section: Discussionmentioning
confidence: 99%
“…While men in substance-disorder treatment programs are often pushed toward job readiness programs to become the "average Joe taxpayer" (Gowan and Whetstone 2012; see also Halushka 2020), women are more typically instructed to resolve flawed desires, emotions, and family relationships, sometimes with the additional goal of workforce participation (Haney 2010;Wyse 2013;Leverentz 2014;McKim 2014McKim , 2017Gurusami 2017;Kerrison 2018a). Programs are also racialized, attempting to mold Black and Latino/a/x populations into a white middle-class norm, placing responsibility for the effects of racism onto racialized people while reading (and treating) white people's drug use through more sympathetic medical lenses (Miller 2014;Gurusami 2017;McKim 2017;Whetstone and Gowan 2017;Dagenhardt 2021;Lindsay and Vuolo 2021).…”
Section: Navigating Strong-arm Sobrietymentioning
confidence: 99%